FAKTOR-FAKTOR PEMILIHAN JURUSAN DENGAN ANALISIS CONTJOINT BERDASARKAN PREFERENSI MAHASISWA JURUSAN MANAJEMEN INFORMATIKA - Dewi Yuliandari; Feri Prasetyo H. (LPPM Universitas Bina Sarana Informatika, 2012)
Department of Informatics management courses are courses and courses that most preferred students AMIK BSI Bekasi, taken from the previous analysis of the factors that most influence according to the research of the Ermayanti (2009) summing up the results of research on SMK selection Department showing the formation of the new factors resulting from analysis of themajor factors in determining the appropriate Factor, is the ability and hope, pleasure, encouragement Factors outside parties, consideration of the Factors of society, Factors appropriate gusto hobby, a factor of economic status, comprehensiveness, parasarana means and support Factors, family Factors, relationship information, favorite Factor and factor in the support of friends. Of factors – these factors which most influenced the decision of the electionDepartment, and in this activity Using quantitative research, with this type of research descriptive research and eksploratori. By using the concept of Conjoint Analysis Is the analysis of the results of activities of mutivarian which will form the patterns to estimate the outcome of the opinion of the respondents.Keywords: Informatics Management, Conjoint Analysis